(untitled) (Mustansiria Dental Journal, 2005)
Objective: study the influence of dietary simulating liquids on the micro hardness , surface roughness, and color stability of polished and non-polished organically modified ceramic, at different storage time . Methods: 240 samples were prepared and then stored in a dark phial containing distilled water (D.W) at 37C for 7 days before conditioning then the samples divided into 3 groups, 80 samples in each, and stared in the conditioning liquids at 40 C for 1, 7 and 41 days At the end of each conditioning time the specimens were subjected to color comparison test, surface roughness test (RA) and microhardness test Vickers hardness number (VHN .) Results & conclusion Increase aging time will increase the VHN value and decrease the Ra value of ormocer specially for the control group (aged in D.W). Aging in ( food stimulated liquids) F SLs produced an increase in VHN value but to a degree less than that of D.W. which in turn produced significant effect of these liquids on Ormocer hardness with time in comparison to the control group Most effect will be seen with 50% Ethanol VHN and color stability. The effect of FSLs on Ormocer VHN were on long term duration (ll days) while for color change ;(7 days) is the critical time and after the first week no additional color will take place. Surface roughness of polished and non - polished Ormocer was not affected by any FSLs and at any aging time. Polishing of Ormocer will increase the VHN value and Ra value for all FSLs and for all time intervals . Change in organic base matrix of composite resins is of great value for improving cmposite properties and durability .